Contextualising sexual health practices among lesbian and bisexual women in Jamaica: a multi-methods study. Issue 52 (1st January 2018) - Logie, Carmen H.; Marcus, Natania; Wang, Ying; Lacombe-Duncan, Ashley; Levermore, Kandasi; Jones, Nicolette; Bryan, Nicolette; Back, Robin; Marshall, Annecka
Abstract: Limited research has examined lesbian and bisexual women's sexual health practices in the Caribbean, where lesbian and bisexual women experience sexual stigma that may reduce sexual healthcare utilisation. We conducted a sequential multi-method research study, including semi-structured individual interviews ( n = 20) and a focus group ( n = 5) followed by a cross-sectional survey ( n = 205) with lesbian and bisexual women in Kingston, Montego Bay, and Ocho Rios, Jamaica. Binary logistic analyses and ordinal logistic regression were conducted to estimate the odds ratios for social-ecological factors associated with lifetime STI testing, sex work involvement, and the last time of STI testing. Over half of participants reported a lifetime STI test and of these, 6.1% reported an STI diagnosis. One-fifth of the sample reported ever selling sex. Directed content analysis of women's narratives highlighted that stigma and discrimination from healthcare providers, in combination with low perceived STI risk, limited STI testing access and safer sex practices. Participants described how safer sex self-efficacy increased their safer sex practices. Quantitative results revealed that a longer time since last STI test was positively associated with depression, sexual stigma, and forced sex, and negatively associated with residential location, perceived STI risk, safer sex self-efficacy, and LGBT connectedness. Selling sex was associated with perceived STI risk, relationship status, sexual stigma, food insecurity, and forced sex. Sexual health practices among lesbian and bisexual women in Jamaica are associated with intrapersonal, interpersonal, and structural factors, underscoring the urgent need for multi-level interventions to improve sexual health and advance sexual rights among lesbian and bisexual women in Jamaica.